Sistem Penjaminan Mutu SMK pada Program Keahlian MPLB dalam Mencapai Penguasaan Keterampilan Abad 21 - Riana Isti Muslikhah; Siti Umi Khayatun Mardiyah; Arwan Nur Ramadhan; Muhyadi; Annisa Harimukti Dian Kurniasari; Dwi Wulandari; Dewi Ayu Ningtyas; Lisa Nuraini; Linta Rosyada; Fitri Nur Handayani (JIMAD: Jurnal Ilmiah Mutiara Pendidikan, 2024)
The advancement of digital technology and the transformation of the labor market require vocational high schools (SMKs) to produce graduates who are not only technically competent but also proficient in twenty-first-century skills. The Office Management and Business Services (MPLB) program requires a quality assurance system capable of supporting the development of critical thinking, creativity, communication, and collaboration skills. This study aims to analyze the implementation of the quality assurance system in SMKs within the MPLB program, examine efforts to strengthen twenty-first-century skills, and identify challenges encountered in its implementation. A descriptive qualitative approach was employed in four public vocational high schools in the Special Region of Yogyakarta through interviews and document analysis. The findings reveal that the quality assurance system is implemented through the evaluation of educational report cards, program monitoring, curriculum alignment with business and industrial partners (DUDIKA), and the strengthening of a school quality culture. The development of twenty-first-century skills is promoted through active and industry-based learning approaches, including Project-Based Learning, Problem-Based Learning, Teaching Factory, and student-centered learning. However, implementation continues to face challenges, including suboptimal coordination, limited teacher competencies, inadequate technological facilities, and insufficient industrial and financial support. The novelty of this study lies in integrating the quality assurance system with the development of twenty-first-century skills specifically within the MPLB program, positioning educational quality not merely toward compliance with standards but also toward the formation of adaptive and work-ready graduates.